Q: If x equals y can square root x plus square root y equals square root x plus y?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Plus or minus the base. If the base is X and you square it, you get X2. If you take the square root of that, you get Plus or Minus X. This is because X*X equals X2 and -X*-X also equals X2.

Yes, because when x equals 1, the square root of x is rational and the square root of -x is irrational, and when x equals -1, the square root of x is irrational and the square root of -x is rational.

Using the quadratic equation formula: x = -3 - the square root of 3 or x = -3 + the square root of 3

x=1/2(-1-square root of 21) and x=1/2(square root of 21 -1)

if x^2 = 49, then the square root property says you can take the square root of both sides as long as you make one a plus-minus. x^2 = 49, which means square root of x^2 = plus minus the square root of 49 the square root of 49 is 7, so +- 7. We get: x = plus/minus 7 (this means either positive 7 or negative 7)

Related questions

Plus or minus the base. If the base is X and you square it, you get X2. If you take the square root of that, you get Plus or Minus X. This is because X*X equals X2 and -X*-X also equals X2.

x = 7

what is the domain of g(x) equals square root of x plus 1? √(x+1) ≥ 0 x+1≥0 x≥-1 Domain: [-1,∞)

y equals x plus 4 when y equals 0 then x equals 2i i is the square root of negative 1

No. The Square root of x is not the value of x. So it can not be simplified beyond: Root X + root 3x Yes. The square root of 3x equals the square root of 3 times the square root of x, so when you add another square root of x, you can factor out the square root of x, thereby simplifying the expression to the square root of x times the sum of one plus the square root of three.

Yes, because when x equals 1, the square root of x is rational and the square root of -x is irrational, and when x equals -1, the square root of x is irrational and the square root of -x is rational.

Using the quadratic equation formula: x = -3 - the square root of 3 or x = -3 + the square root of 3

x=1/2(-1-square root of 21) and x=1/2(square root of 21 -1)

square root of 4x is 2 times square root of x, so answer is square root of x times 3 since it is 2 square roots of x plus one of them

if x^2 = 49, then the square root property says you can take the square root of both sides as long as you make one a plus-minus. x^2 = 49, which means square root of x^2 = plus minus the square root of 49 the square root of 49 is 7, so +- 7. We get: x = plus/minus 7 (this means either positive 7 or negative 7)

If x equals the square root of ...., then you already have solved for x

6x^2=84, x^2=14, root(14) = x x = Plus or minus square root of 14, or 3.741...